MUSIC AESTHETIC AND LIFE LIVING: CASE STUDY MR. MAIROM THAMMACHATI-ASOKA - พิมพ์เสน วรพงษ์; สละวาสี วรธรรม (Journal of Humanities, Social Sciences, and Arts, 2023)
Abstract The article entitled ’Music aesthetic and life living: a case study Mr.Mairom Thammachati-asoka was presented the musical aesthetic and the philosophy of thinking in the living of Mr.Mairom Thammachati-asoka. Applying the aesthetic principle based on documents, books, and the online interviewing related to Mr.Mairom’s works were involved. It was found that almost all of Mr.Mairom Thammachai-asoka performances were different from the common way of using the ukulele and singing. The lyrics were used to narrate about art, life, nature, and love. The beauty of aesthetic music was based on the interpretation of the audience whose experience was about time, places, and societies at that time. Mr.Mairom Thammachati-asoka focused on the principal of thinking and the way of life emphasizing on the natural peacefulness. Key words : Aesthetic, Beauty, Music, Mr.Mairom Thammachati-asoka